The impact of impulsivity and social factors on pathological gambling. - Zheng, Ling Qin. (2012)
Increased in prevalence of pathological gambling have been a worldwide phenomenon. With the development of the Integrated Resort in Singapore as well as the growth of Internet gambling, we are experiencing an increase in pathological gambling rates. This study aims to examine the role of impulsivity, accessibility to gambling, peers and parental influence as well as religiosity on pathological gambling. Motor, trait as well as cognitive impulsivity has been found to have an impact on pathological gambling. Accessibility to gambling, specifically; proximity to gambling places and ease of use has been found to be positively correlated to rate of problem gambling. A mixed result has been found for the relationship between number of gambling machines and pathological gambling. Imposition of conditions to entry has been reported to be ineffective in reducing problem gambling. Adolescents with peers or parents who gambled were found to higher inclination to problem gambling. Lastly, religiosity seems to play a role in preventing gambling behaviors with some mixed results.